Multifunction cooler box for indoor and outdoor usage application / Hanis Nabilah Khairul Nizam and Radzi Abdul Rasih - Khairul Nizam, Hanis Nabilah; Abdul Rasih, Radzi (School of Mechanical Engineering, 2023)
The existing cooler box has a limited ability to maintain temperature, particularly when placed outside of the house. Therefore, this project aims to address this issue by designing and constructing an improved cooler box capable of sustaining temperature even in outdoor settings during hot and sunny days. The enhanced cooler box incorporates a foldable table and utilizes the peltier cooling effect. Additionally, it is equipped with a rechargeable battery and power supply. This practical product is suitable for both indoor and outdoor applications, allowing users to store cold drinking water that will remain chilled for extended periods. The primary beneficiaries of this product are travelers and backpackers engaging in outdoor activities, as it enables them to enjoy refreshing cold water whenever needed.